Señora Rodríguez and other worlds - Cerda, Martha; Jiménez-Andersen, Sylvia (Durham Duke University Press, 1997)
"Cerda's Señora Rodríguez and other worlds is a playful, parodic, and often sarcastic tale of a woman, her magical purse, and the other worlds that may or may not be closely linked to the protagonist. Novel or collection of short stories? Both English- and Spanish-language critics are uncertain. The translator gives no hints either"--Handbook of Latin American Studies, v. 58.
Tac-2693g donated by Mary Grace Concepcion [Ma. Mimietta S. Bagulaya] on 16 Sep 2016.